Marketing Mix Strategy in Al-Qur'an Perspective - Achmad, Yudianto; Edy, Sarwo (Proceeding International Pelita Bangsa, 2023)
The rapid development of sharia-based business in the world and in Indonesia, among others, is shown by the many opportunities open to sharia business, which requires various companies to aggressively develop marketing mix strategies for their products that apply sharia principles. The main basis of sharia principles is based on values or substantive content contained in various surahs and verses of the Qur'an, as well as hadiths, all of which are related to the values of sharia business principles. Meanwhile, the marketing mix theory states that there are 4 variables in marketing, known as the "4P" variables, namely; Product, Price, Place, Promotion whose values have been widely taught in various universities, and have been widely implemented by various companies in the world to devise a form of marketing mix strategy in an effort to win the competitive market for their respective products. On the other hand, the Al-Qur'an as the main basis of sharia principles, it is suspected that among its various surahs and verses, it has substantive content that is similar to the values in the “4P” variable Marketing, so that it can be used to develop a marketing mix strategy from Al's perspective. -Quran. The Writing based on this literature study reveals that there is substantive content between surahs and verses of the Qur'an which has a real resemblance to the values in the "4P" variable of Marketing so that a form of marketing mix strategy from an Al-Qur'an perspective is structured.